Ethical Reflections on Quantified Self Devices and their Effects on Humans - Nora Berg (2019)
This thesis reflects ethical consequences of quantified self devices. Thereby, it focuses mainly on the effects on users and society. Contemporary incentives for self-optimization, constant tracking of physiological data, and feedback to users create devices which are morally questionable, since positive effects could mainly be found in certain best case scenarios. Furthermore, quantified self devices have the capability to even harm users. Instead of the contemporary design assumptions, new baselines are elaborated, which aim to maintain the respective ethical values and psychological knowledge about feedback and behavior change. These baselines intend to maintain values as autonomy, privacy, transparency, and others to find ways which support individual human growth and happiness. The argumentation unfolds alongside a critical design concept of a smart dress and its respective userstory. Insights from sociology, psychology and ethics are used to evaluate design concepts, assumptions, and possible impact on users.